Ni@4H-chromene-based core–shell nanoparticles: highly sensitive and selective chemosensors for the radiosensitizer bromodeoxyuridine. Issue 31 (21st July 2022) - Bhardwaj, Geetika; Kaur, Randeep; Saini, Sanjeev; Kaur, Navneet; Singh, Narinder
Abstract : The present sensor fulfils all the conditions of an efficient sensor (easy, cost effective, low detection limit and diverse) as it can be evaluated via different methods (UV-visible absorption, fluorescence, cyclic voltammetry and circular dichroism). Abstract : Regardless of the significant use of 5-bromo-2′-deoxyuridine (BrdU) as a radiosensitizer and diagnostic tool in cancer patients, some severe side effects and health issues have been reported, such as genetic mutations, birth defects, and other inheritable genetic effects. Thus, it has become more important to quantify the amount of BrdU during its usage. With reference to this, Ni@4 H -chromene (Ni@G1 )-based core–shell nanoparticles have been fabricated and these show a great response for the selective and sensitive detection of BrdU. The formed Ni@G1 exhibits no significant response with interfering thymidine analogs like iododeoxyuridine (EI) and ethynyl deoxyuridine (EdU) in competitive binding studies. Ni@G1 shows the ability to sense BrdU up to a detection limit of 9 nM and no significant interference is shown by pH, salt and temperature. A comparison of studies in aqueous and organic media further reveals that the sensor reported here shows an excellent response in an aqueous medium.